ANALISIS KEBIJAKAN PENDIDIKAN DASAR ISLAM DARI PERSPEKTIF PEMBELAJARAN TEMATIK TERPADU - Asriana Harahap (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2020)
The purpose of this paper is to present the importance of education policy analysis in Islam from the perspective of integrated thematic learning. The methodology or approach used in this method uses library research methods or approaches, while data collection is carried out by examining or exploring several journals, books and documents (both printed and electronic) as well as other sources of data and information. considered relevant to the study. The findings in this study are, thematic / integrated learning offers learning models that make learning activities relevant and meaningful for students, both formal and informal activities, including active inquiry learning through passive absorption of knowledge and facts, by empowering knowledge and student experience to help him understand and comprehend the world of his life. This way of packaging learning experiences designed by the teacher will greatly affect the meaningful experiences of students and make the learning process more effective and interesting. The conceptual links studied with the contents of other relevant fields of study will form a schemata, so that wholeness and unanimity of knowledge will be obtained. The acquisition of wholeness of learning, knowledge, and unanimity of views about life and the real world can only be reflected through integrated learning. Thematic / integrated learning is a learning model that combines several learning materials from various competency standards and basic competencies from one or several subjects. The application of this learning can be done through three approaches namely determination based on the interrelation of competency standards and basic competencies, themes and problems encountered.